1983
DOI: 10.1590/1809-43921983131073
|View full text |Cite
|
Sign up to set email alerts
|

ESTUDO SOBRE O ESTADO NUTRICIONAL EM RELAÇÃO AO ZINCO NA AMAZÔNIA. I. Níveis de Zinco no Sôro e Ingestão de Zinco em Operários de Manaus, 1978 ()

Abstract: SUMARIOO objetivo deste estudo foi verificar se a baixa Ingestão de zinco relatada para a população da área urbana da cidade de Manaus, no Estado do Amazonas, está associada com níveis baixos de zinco sé-rico. O estudo foi realizado com trabalhadores percebendo salários baixos, em quatro fábricas de Manaus. Duas destas fábricas forneciam alimentação e assistência médica. A média e a mediana da ingestão de zinco dietético, foi 54.7% e 49.3% respectivamente das recomendações diárias, americanas. A ingestão de zi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
3

Year Published

1992
1992
2019
2019

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 9 publications
0
3
0
3
Order By: Relevance
“…Analysis of the data from a household expenditure survey conducted in Manaus in the mid-seventies, found that zinc was one of the most deficient nutrients among the household diets (Shrimpton, 1984). Further studies at that time, found that a third of low-income urban workers in Manaus had low serum zinc levels associated with inadequate dietary intakes (Shrimpton, et al, 1983). Zinc supplementation trials carried out among poor urban Amazonian mothers in the early eighties, showed positive effects on both zinc and vitamin A levels of their breast milk, as was published just recently (Shrimpton and Marinho 2018).…”
Section: Introductionmentioning
confidence: 87%
“…Analysis of the data from a household expenditure survey conducted in Manaus in the mid-seventies, found that zinc was one of the most deficient nutrients among the household diets (Shrimpton, 1984). Further studies at that time, found that a third of low-income urban workers in Manaus had low serum zinc levels associated with inadequate dietary intakes (Shrimpton, et al, 1983). Zinc supplementation trials carried out among poor urban Amazonian mothers in the early eighties, showed positive effects on both zinc and vitamin A levels of their breast milk, as was published just recently (Shrimpton and Marinho 2018).…”
Section: Introductionmentioning
confidence: 87%
“…Dados limitados sobre absorção de zinco da dieta total em humanos sugerem uma influência do fitato mais moderada, resultando em 26% a 33% de absorção desse mineral em dietas com razões molares de 14 e 5, respectivamente 26 , e 29% de absorção em dietas com razão molar de 7 27 . Estudo realizado com mulheres caucasianas australianas revelou que, embora o consumo médio de zinco no grupo de vegetarianas fosse significantemente menor que nas onívoras, as médias de concentrações de zinco sérico eram similares nos dois grupos 1 .…”
Section: I S C U S S ã Ounclassified
“…A deficiência de zinco em dietas de regiões menos desenvolvidas no Brasil tem sido descrita na literatura 27 . Tal deficiência está associada, principalmente, a déficit de crescimento, hipogonadismo, infertilidade, depressão do sistema imune, redução do paladar e do apetite 29 , e afeta cerca de 2 bilhões de pessoas, predominantemente, crianças e gestantes nos países em desenvolvimento 30 .…”
Section: I S C U S S ã Ounclassified
“…In the 1980s, zinc was found to be one of the principal dietary inadequacies in the central Amazon valley (Shrimpton 1980;Shrimpton 1984;Amoroso & Shrimpton 1984), and a third of low-income urban workers had low serum zinc levels (<70 mg/l), associated with similarly inadequate dietary intakes (Shrimpton et al 1983a). The population was typically stunted, but there was not the dwarfism and sexual retardation, nor the other overt clinical signs of zinc deficiency found in the middle east (Prasad et al 1961).…”
Section: Introductionmentioning
confidence: 99%